Requirements for Becoming a Startup: A Study with an Economic Sociology Approach (Case Study: Managers of Startups in Isfahan City) - Rahmatollah Torkan; Seyed Samad Beheshty; Ramin Moradi (جامعه شناسی کاربردی, 2025)
IntroductionIn today's fast-paced world, the growing dynamics of the global economy, society, and technology have given rise to new business models. Among these, startups have emerged as vital engines of economic development due to their innovative potential. These emerging companies contribute significantly to job creation and economic advancement by introducing creative business models and cutting-edge technologies. However, like many social phenomena, business paradigms are evolving. A notable trend is the increasing recognition of startups as the key drivers of economic growth and innovation, attracting international attention as countries strive to enhance their startup ecosystems. Iran is no exception to this movement with various initiatives aimed at developing its startup sector. Despite this progress, much of the existing research on startups has overlooked the specific requirements for their establishment in particular contexts, often taking a generalized approach. Additionally, many studies have focused on macro-level analyses, neglecting a deeper understanding of the perspectives of individuals involved in this field at the micro level. To address these gaps, the present study aimed to analyze the process of becoming a startup and the associated contexts and requirements in the city of Isfahan, utilizing an economic sociology framework. By concentrating on the viewpoints of startup managers, this study sought to provide a clearer understanding of these requirements within this specific context.  Materials & MethodsThis qualitative research grounded in the interpretive paradigm and utilizing the thematic network approach (Attride-Stirling, 2001) was designed to uncover meaningful patterns within the data. The study population consisted of all startup and knowledge-based company managers in the city of Isfahan. From this group, 14 experienced managers of active startups—each with a minimum of 5 years in innovation and technology—were selected through purposive sampling to provide rich, in-depth insights on the topic. Data collection was conducted via semi-structured in-depth interviews from early April to late November 2024. These discussions centered on the managers' experiences in the startup formation process and their identification of key requirements from their perspectives. The data were analyzed using MAXQDA 2020 software, following the systematic steps of the thematic network approach, which included initial coding, organizing themes at both basic and global levels, and explicating the organizing themes while mapping the relationships between them. To enhance the credibility and reliability of the research findings, two key mechanisms were employed: member checking to confirm that the findings accurately reflected the participants' experiences and an independent evaluation by an external auditor familiar with qualitative research methods and economic sociology, ensuring an impartial review of the analysis process. Discussion of Results & ConclusionThe analysis of startup managers' perspectives in Isfahan highlighted that the requirements for becoming a startup could be encapsulated within a comprehensive theme: "Becoming a Startup as an Innovation Ecosystem". This overarching theme elucidated the formation and development of a dynamic, interactive network composed of diverse structural, individual, micro-, macro-, and economic-social elements, all of which contributed to the growth and success of entrepreneurship in the form of startups within a specific geographical area. This innovative ecosystem functioned as a coordinated and synergistic system.The key organizing themes within this ecosystem included:Startup Ecosystem: Encompassing innovative policymaking structures, startup legislation, supportive government initiatives, internationalization, and the startup communityStrategic Idea: Serving as an innovative and market-reality-based foundationStartup Mentality: Reflecting the leadership, entrepreneurial spirit, and risk-taking attributes of foundersAffinity of Strategic Financial Approach: Manifested in funding strategies and the alignment between investors and foundersTeam Dynamics: Emphasizing the importance of teamwork and specialized division of laborMarket Realism: Informed by accurate analyses of customer needsStartup Networking: Focusing on creating and strengthening connectionsAccording to the managers of Isfahan startups, the formation, strengthening, and sustainability of these ventures relied on the interaction and synergy of these organizing themes at various levels. A robust startup ecosystem created a comprehensive platform that connected all elements and, through diverse supports, bolstered innovation and sustainability of startups. Within this framework, the strategic idea served as the initial catalyst, while the startup mentality embodied the essential characteristics of founders. Financial affinity acted as a critical survival factor, team dynamics provided the driving force, market realism guided actions, and networking served as a lever for development. Together, these components facilitated the process of becoming a startup in conjunction with the startup ecosystem. In conclusion, "Becoming a Startup as an Innovation Ecosystem" illustrated the interconnectedness and synergy of essential requirements for innovation. Without the presence and mutual interaction of these elements at various layers of business, the process of establishing a startup might be hindered or indefinitely delayed.